Modern extracorporeal circulatory support systems (centrifugal pumps and oxygenators). Literature review - O. Yu. Esipova; A. P. Kuleshov; V. K. Bogdanov; A. S. Esipov; N. V. Grudinin (Вестник трансплантологии и искусственных органов)
For more than 70 years, short-term mechanical circulatory support devices, as well as methods and skills for their implantation, have been continuously developed and improved. An in-depth study of each of the existing devices is important not only to optimize patient outcomes, but also to create a safer, more effective, smallersized new device. This review considers existing temporary circulatory support devices, as well as oxygenators, that supplement the system to protect lung function. Their main technical characteristics and the peculiarities of their application in clinical practice are given. Based on the literature review, we formulated the main directions of extracorporeal membrane oxygenation evolution in Russia.